Transcroporal Artificial Urinary Sphincter Placement With Closure of Corporal Bodies—A Long-Term Analysis of Functional Outcomes - Maurer, Valentin; Dahlem, Roland; Howaldt, Marian; Riechardt, Silke; Fisch, Margit; Ludwig, Tim A.; Engel, Oliver (Frontiers in Surgery, 2022)
Objectives: The artificial urinary sphincter (AUS) is the gold-standard for postoperative stress urinary incontinence (SUI). The transcorporal AUS (TC) placement constitutes the main salvage option in high-risk patients suffering from SUI with fragile urethras. Literature analyzing long-term outcomes with respect to explantation rates, continence and erectile function are scarce. Methods & patients: Retrospective data collection was performed since 2011. TC were applied according to a standardized protocol. TC were implanted after bulbar urethroplasty or double-cuff (DC) explantation. After TC-placement, the tunica albuginea was closed in order to minimize the risk of postoperative bleedings and erectile dysfunction. Activation was performed 6 weeks postoperatively. Further follow-up (FU) was scheduled 6/ 24 months postoperatively and every two years thereafter. Primary/ secondary endpoints were explantation/ continence rates. Thereupon postoperative bleedings and erectile function were analyzed. Results: 39 high-risk patients were available for analysis. Median age was 72 years. 84.6%, 10.3% and 2.6% had a history of radical prostatectomy, TURP or radical cystectomy, respectively. 61.5% had a history of radiation therapy of the prostate. 41% had a history of urethral surgery. 95% were status after DC explantation. Median FU was 27 months. Objective, subjective and social continence were 54.5%, 69.7% and 78.8%. Mean pad usage was 1.8 pads/d. Only one patient suffered from a postoperative hematoma. 15.4% of the patients were able to have an erection preoperatively, compared to 7.7% after TC placement. Estimated mean explantation-free survival of the TC was 83 months in the Kaplan-Meier analysis. Conclusions: TC AUS implantation constitutes a viable salvage approach in high-risk SUI patients with mean device-survival of almost 7 years and high social continence rates of almost 80%. An intraoperative closure of the tunica albuginea after TC placement allows for very low rates of postoperative hematoma and supports postoperative erectile rigidity.